Effect of different processing techniques on nutrient and anti-nutrient compositions of plant feedstuffs for their probable use as aqua-feed ingredients - Mandal, Sudipta; Ghosh, Koushik (Journal of the Inland Fisheries Society of India, 2021)
We made an attempt to compare between conventional (i.e. heat-treatment and soaking in water) and bio-processing strategies for processing of two plant feedstuffs, viz., groundnut oil cake (GOC) andÂ Pistia leaves (PL) for their probable use as non-conventional aqua-feed ingredients. Conventionally, dried and ground plant feedstuffs were either heat-treated by autoclaving (15 lb, 121Â°C, 30 min), or soaked in water (1:5 w/v, 12h). Bio-processing was done through solid state fermentation (SSF) by a yeast strain Pichia kudriavzevii (GU939629) isolated from the gut of a freshwater fish Cirrhinus mrigala. SSF was superior in terms of both improving nutritional components as well as reducing some anti-nutritional factors (ANFs). Analysis of proximate composition of GOC and PL following SSF for 15 days under optimized conditions revealed significant (P < 0.05) increase in the contents of crude protein, lipid, minerals, free amino acids and fatty acids concurrent with reduction in the contents of tannin and other ANFs. On the contrary, soaking and autoclaving negatively affected crude protein, lipid, total free fatty acid, ash and most of the minerals. Though concentration of the ANFs decreased as a result of soaking and autoclaving also, the degree of reduction was much less as compared to the SSF. Therefore, SSF by P. kudriavzevii might be consideredÂ as a better option than traditional processing techniques (viz., soaking and autoclaving) in improving the nutritional value of the plant feedstuffs. Key words Non-conventional aqua-feed ingredients, Solid state fermentation, Soaking, Autoclaving, Ground nut oil cake, Pistia leaves